From global to local scales in galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Sánchez, Sebastian F.; Lopez Cobá, Carlos
Abstract: We summarize here some of the results reviewed recently by Sanchez (2020) comprising the advances in the comprehension of galaxies in the nearby universe based on integral field spectroscopic galaxy surveys. In particular we explore the bimodal distribution of galaxies in terms of the properties of their ionized gas, showing the connection between the star-formation (quenching) process with the presence (absence) of molecular gas and the star-formation efficiency. We show two galaxy examples that illustrates the well known fact that ionization in galaxies (and the processes that produce it), does not happen monolitically at galactic scales. This highlight the importance to explore the spectroscopic properties of galaxies and the evolutionary processes unveiled by them at different spatial scales, from sub-kpc to galaxy wide.